INFLUÊNCIA DO TEOR DE ÁGUA E DA GRANULOMETRIA DO AGREGADO MIÚDO NAS PROPRIEDADES DO ESTADO FRESCO DE ARGAMASSAS ESTABILIZADAS - Silva, Amanda Cardoso da; Calçada, Luciana Maltez; Betioli, Andrea Murillo; Oliveira, Alexandre Lima de; Casali, Juliana Machado (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The objective of this work is to evaluate the influence of water content and fine granulometric aggregate on the fresh state properties of ready mix mortars. Three samples of fine aggregate were analyzed: sand without sieving, one with grains passing through the sieve 1.2 mm and the other with passing grains in the sieve 0.6 mm. The mortars were produced with the same content of hydration stabilizing admixtures and air-entrained admixtures with three water / dry material ratios. The properties of the fresh state of ready mix mortars were evaluated as consistency index, specific gravity and air entrained content. These properties were evaluated in three storage durations: 0, 24 and 48 hours. It was observed that an increase of the consistency when comparing the results obtained for mortar A (reference) and mortar A 0.6. There was a loss of consistence of the ready mix mortar throughout the storage duration, independently of the granulometry studied. The highest values of air entrained content were obtained for mortars with finer grain size, comparing mortars with the same water/ dry materials ratio. Thus, it is necessary to observe the granulometric distribution of the small fine aggregates in the dosage of ready mix mortars.